Benign schwannoma of peroneal superficial nerve: From bedside to benchside. Issue 1 (January 2019) - Squintani, G.; Basaldella, F.; Tramontano, V.; Sala, F.; Bonetti, B.; Masotto, B.
Abstract : To evaluate the importance of multidisciplinary approach in peripheral nerve diseases. We describe a man who came to our attention for tingling and pain in the distal part of his left leg and dorsal aspect of his foot. He was submitted to clinical examination, lumbar and leg MRI, EMG and ultrasound before surgery. Clinical examination revealed a small 'ball-like' mass in the distal third of the leg between extensor digitorum longus muscle and peroneus brevis muscle. Imaging revealed a schwannoma/neuroma of the left superficial peroneal nerve (7 mm × 11 mm, 0.683 cm 2 with ultrasound). EMG revealed a mild neuropathy of left peroneal superficial nerve with predominant sensory impairment. The patient was operated with intraoperative monitoring and mapping with favourable outcome and pain resolution. Histology was compatible with benign schwannoma. Multidisciplinary approach is recommended for the diagnosis and management of peripheral nerve benign tumors.